Changes in bovine milk fat globule membrane proteins caused by heat procedures using a label-free proteomic approach. (November 2018) - Yang, Yongxin; Zheng, Nan; Zhao, Xiaowei; Yang, Jinhui; Zhang, Yangdong; Han, Rongwei; Qi, Yunxia; Zhao, Shengguo; Li, Songli; Wen, Fang; Guo, Tongjun; Zang, Changjiang; et al.
Abstract: The milk fat globule membrane (MFGM) plays an important role in stabilizing fat in the aqueous phase, and the components of this membrane are involved in multiple biological functions. Here, we investigated changes in the protein composition of the MFGM fraction between raw and heated whole milk using a label free proteomic approach. In total, 612 MFGM-related proteins were identified in all groups. Compared with raw milk, the number of proteins that were not identified in the MFGM fraction was increased from pasteurized milk to ultra-high-temperature milk, whereas the number of milk proteins incorporated into the MFGM fraction was similar among heated groups. The abundances of several milk proteins (β-lactoglobulin and β-casein) were increased in the heated milk groups in a temperature-dependent manner. From our functional analysis, proteins that were not identified in the MFGM fraction of heated milk were mainly associated with multiple biological functions. These findings provided novel insights into the effects of heat procedures on MFGM protein components and their potential physiological functions, thereby yielding data on the appropriate heating procedures to use for raw milk. Graphical abstract: Highlights: Distinct protein properties were identified in different types of heated whole milk. Heat caused downregulation of proteins of milk fat globule membranes. Milk proteins were incorporated into milk fat globule membranes following heating.